NETIQUETTE: Penguatan Soft Skill Netizen untuk Generasi Berkarakter - Lilis Erna Yulianti (JIRA: Jurnal Inovasi dan Riset Akademik, 2021)
The virtual world is not a world without borders so we are free to do anything. But as in the real world that has norms, ethics and etiquette, in cyberspace also requires a netiquette. Netiquette as a healthy internet moral regulation is needed so that digital communication between netizens runs harmoniously and respect each other and away from conflict and deviant behavior so as to make the lives of netizens become more comfortable (comfort life). The implementation of netiket if done continuously in the long term will have a positive impact on netizens and their social environment. The positive impact for netizens towards strengthening their soft skills will form a generation of character, integrity, morality, having a healthy mentality, and getting appreciation from others who can be reinforcement for him to continue to do good to others. The positive impact on the environment makes interactions in the social environment healthier in more human communication patterns in their interaction patterns.In fact, there are still many disputes, violations and crimes that are implicated in social media and online media. For example: the rise of pornographic content, hate speech content, hoax issues, cyberbullying, insults, online fraud, digital sexual crimes, child trafficking, online prostitution, and various other cyber crimes. Based on the problems in the virtual world, the research entitled "Netiquette Strengthening Soft Skills Netizens for Generation of Character" aims to compare the phenomenon of ethical violations in social media and online media conducted by netizens associated with ethical guidelines in cyberspace (netiquette). This research uses qualitative methods with a literature review approach.